Exercise of professional autonomy of intensive care nurses in the pandemic scenario - Rafaela Lira Mendes Costa; Regina Maria dos Santos; Isabel Comassetto; Maria Ligia dos Reis Bellaguarda (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To analyze the exercise of professional autonomy of intensive care nurses during times of the new coronavirus pandemic. Method: A descriptive, qualitative study, conducted with 19 nurses from Intensive Care Units of two public hospitals and one private hospital. The information was produced from October 2020 to January 2021, through semi-structured interviews, using content analysis in thematic modality, guided by Eliot Freidson's Sociology of Professions. Results: Nursesargued that it was difficult, amidst the pandemic, to act with all the prerogatives assigned to them by their social mandate, for various reasons, such as limited knowledge about the disease, fragile teamwork communication, and scarcity of material and human resources. Conclusion: The exercise of professional autonomy is shaped by the confrontation of multiple factors that impact the performance of intensive care nurses, especially in a context of pandemic crisis.